Are SMEs Prepared for the Crisis, as the Biggest Companies Are? - Bekeris, Rokas (Publishing House of the Wrocław University of Economics, 2009)
Decreased consumption is the biggest problem for SMEs. Administrative barriers and lack of labour force together with its high price could be mentioned as the two most important obstacles to do business. Meanwhile the big companies are not so preoccupied about decreasing of buying power but they are more interested in administrative questions and lack of labour force. The biggest EU companies export more actively than small ones. The main possibility for SMEs to compete with large companies is finding out niche on the market. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 67-74